Optimization of Sandwich Bumper for Three Year Old Child Neck Injury Prevention - Rafukka, I. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Impact energy absorption vehicle components play an important role in reducing severity of injury in vehicle crashes. Children being delicate are most vulnerable in vehicular collisions. The neck is the major body region after head that experiences a high moment when deceleration is transmitted to it. Bumper is one of the vehicle’s frontal energy absorption components that reduce deceleration to the occupants. Sandwich bumper is an energy absorption component that could substitute a steel bumper. The geometry of the sandwich bumper affects its energy absorption capability on impact. This work applies an optimization technique to determine the sandwich bumper thicknesses that provides lower neck moments to child on impact at 48km/h in LS DYNA code. Finite element (FE) simulations using crash dummy models being the simplest method to reproduce accident was employed. The optimization results found the minimum neck moment of 25.4 Nm occurred at foam thickness of 68.76 mm and bumper thickness of 2 mm. The study provides designers with quantitative information on how the bumper performance affects child injury in vehicular frontal crashes. This will lead to design of safer vehicles for the children population.